Das ideias de Roland Barthes à teoria do enquadramento: análise de uma cobertura política - D'Arcadia, João Guilherme da Costa Franco Silva [UNESP] (2014)
This research aims at searching for the ideas' verification of the semiotician Roland Barthes for analysis f mass communication media. It seek the identification of rethorical operators of myth, described in Mythologies, and the elements of the authoritarian language - presented in Leçon - in the narratives produced by the press. Therefore, there were analysed articles from Folha d S. Paulo and O Estado de S. Paulo published on the subsequent week of the prison of the first defendants convicted on criminal action 470, resulted from the alleged bribery payments to parliamentarians in the well-known mensalão case. Eventual biases and implicit intentionalities by both newspaper were found through frame analysis, in which was possible to categorise specific textual properties that exemplify the rhetorical operators of myth. The study came to the conclusion that several revealed characteristics are inherent to the journalistic production - such as omission of history that descontextualises events which turn out to be self-existent - and quality quantification which searches for describing events in a generic and quantitative form. At last, the research interprets that both newspapers' coverages are similar and reinforce the figures of authority and social institutions, which is also a daily journalism's characteristic